Women’s participatory communication in mangrove ecotourism for climate mitigation - Miftahul Huda; Ahmad, Maghfur; Muniroh, Siti Mumun; Anggraeni, Dewi; Suharto, Slamet; Arumaisha, Alfa Mulia; Wahab, Abdul (Faculty of Communications Science, Dr. Soetomo University, 2026)
As a result of climate change, the Mulyorejo Village in Pekalongan is a coastal area that is frequently affected by tidal flooding (rob). In response, the community has initiated mangrove-based ecotourism initiatives to protect the environment and strengthen socio-ecological resilience. This study explores the role of women's participatory communication in driving these initiatives, examining how dialogic communication and community deliberation shape everyday ecological practices. A qualitative case study approach was employed to collect data through participatory observation, interviews with women’s group leaders, ecotourism managers and community elders, and field documentation. The findings reveal that women play a central role in environmental education, ecotourism management and local policy advocacy. Key community innovations include the Mangrove School, which turns local knowledge into ecological action; the Kliwonan Market, which supports outreach and sales of mangrove-based products; and programmes such as aquaculture and the Waste Bank, which strengthen food security and recycle waste into mangrove fertiliser. These initiatives demonstrate how participatory communication can drive ecological democracy and inclusive sustainability through women’s leadership and intergenerational collaboration.